Kallikrein-like amidase activity in renal ischemia and reperfusion - Carattino,M.D. (2000)
We assessed a kallikrein-like amidase activity probably related to the kallikrein-kinin system, as well as the participation of leukocyte infiltration in renal ischemia and reperfusion. Male C57BL/KSJmdb mice were subjected to 20 or 60 min of ischemia and to different periods of reperfusion. A control group consisted of sham-operated mice, under similar conditions, except for ischemia induction. Kallikrein-like amidase activity, Evans blue extravasation and myeloperoxidase activity were measured in kidney homogenates, previously perfused with 0.9% NaCl. Plasma creatinine concentration increased only in the 60-min ischemic group. After 20 min of ischemia and 1 or 24 h of reperfusion, no change in kallikrein-like amidase activity or Evans blue extravasation was observed. In the mice subjected to 20 min of ischemia, edema was evident at 1 h of reperfusion, but kidney water content returned to basal levels after 24 h of reperfusion. In the 60-min ischemic group, kallikrein-like amidase activity and Evans blue extravasation showed a similar significant increase along reperfusion time. Kallikrein-like amidase activity increased from 4 nmol PNA mg protein-1 min-1 in the basal condition to 15 nmol PNA mg protein-1 min-1 at 10 h of reperfusion. For dye extravasation the concentration measured was near 200 µg of Evans blue/g dry tissue in the basal condition and 1750 µg of Evans blue/g dry tissue at 10 h of reperfusion. No variation could be detected in the control group. A significant increase from 5 to 40 units of DAbs 655 nm g wet tissue-1 min-1 in the activity of the enzyme myeloperoxidase was observed in the 60-min ischemic group, when it was evaluated after 24 h of reperfusion. Histological analysis of the kidneys showed migration of polymorphonuclear leukocytes from the vascular bed to the interstitial tissue in the 60-min ischemic group after 24 h of reperfusion. We conclude that the duration of ischemia is critical for the development of damage during reperfusion and that the increase in renal cortex kallikrein-like amidase activity probably released from both the kidney and leukocytes may be responsible, at least in part, for the observed effects, probably through direct induction of increased vascular permeability.